The Effect of Price and Quality on Customer Loyalty PT HM Sampoerna Tbk - Fauzan Yusuf; Mahir Pradana (STIE Amkop Makassar, 2023)
This study aims to analyze how the Effect of Price and Product Quality on Consumer Loyalty PT HM Sampoerna Tbk. This study uses a quantitative approach with descriptive and associative causal research types. The sampling technique in this study was respondents totaling 100 people with non-probability sampling techniques with purposive sampling methods. Data were analyzed by descriptive analysis and multiple linear regression analysis using IBM SPSS Version 25 software. Based on the results of descriptive analysis, the overall price variable is in a good category. The overall Product Quality variable is in a good category. As well as the overall Consumer Loyalty variable is in a good category. The results of multiple linear regression analysis on the effect of Price and Product Quality on Consumer Loyalty amounted to 68.1% and the remaining 31.9% were influenced by other variables that were not studied in this study.